2017
DOI: 10.1007/s11117-017-0506-9
|View full text |Cite
|
Sign up to set email alerts
|

Some applications of the regularity principle in sequence spaces

Abstract: Abstract. The Hardy-Littlewood inequalities for m-linear forms have their origin with the seminal paper of Hardy and Littlewood (Q.J. Math, 1934). Nowadays it has been extensively investigated and many authors are looking for the optimal estimates of the constants involved. For m < p ≤ 2m it asserts that there is a constantand all positive integers n. Using a Regularity Principle recently proved by Pellegrino, Santos, Serrano and Teixeira, we present a straightforward proof of the Hardy-Littewood inequality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 18 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Recently, W.V. Cavalcante has shown that (4.1) is a consequence of the inclusion result for multiple summing operators due to Pellegrino et al combined with Theorem 5 (see [10]). The standard isometries between L(X p , X) and ℓ w p * (X), for 1 < p ≤ ∞, allow us to read the previous Theorems 5, 6, 7 as coincidence results (see [12]).…”
Section: Applications: Hardy-littlewood's Inequalitiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, W.V. Cavalcante has shown that (4.1) is a consequence of the inclusion result for multiple summing operators due to Pellegrino et al combined with Theorem 5 (see [10]). The standard isometries between L(X p , X) and ℓ w p * (X), for 1 < p ≤ ∞, allow us to read the previous Theorems 5, 6, 7 as coincidence results (see [12]).…”
Section: Applications: Hardy-littlewood's Inequalitiesmentioning
confidence: 94%
“…The Hardy-Littlewood inequalities have been investigated in depth in the recent years (see, for instance, [1,2,3,4,10,11,13,17,19,21,22]). Here X p stands for ℓ p if p < ∞ and X ∞ := c 0 .…”
Section: Applications: Hardy-littlewood's Inequalitiesmentioning
confidence: 99%
“…The Hardy-Littlewood inequalities consist in optimal extensions of Littlewood's 4/3 inequality [17] (originally stated for c 0 spaces). In the last years the interest in this subject (which can be considered part of the theory of multiple summing and absolutely summing operators) was renewed and several authors became interested in this field ( [1,2,3,6,7,20,22,23]).…”
Section: Introductionmentioning
confidence: 99%
“…Khintchine inequality is originally a result from probability, but it is also frequently used in Analysis and Topology (see [5,7,10,11,12,13,21]). The importance of the Rademacher functions and the Khintchine inequality in Functional Analysis lies mainly on the fact of its utility in the study of the geometry of Banach spaces (see [5,10,12]).…”
Section: Introductionmentioning
confidence: 99%
“…The original purpose of this inequality is to provide a unimodular form on (ℓ n p ) d with relatively small supremum norm but relatively large majorant function [12]. Nowadays this result is a formidable tool in modern analysis with a broad range of applications (see, e.g., [1,2,4,7,13,14,15,16,18,19]).…”
mentioning
confidence: 99%